The Determinants of Corpotate Cash Holdings: An Empirical Investigation of UK Firms - Lu, J (2011)
This paper investigates the determinants of the cash holdings of UK firms over the period of 1997 to 2007. Through analysis of time effect, this study finds that the trend of cash holdings for sample firms are tend to be stable during the sample period, and also moving parallel with the trend of leverage ratio, indicating a potentially positive relationship. With respect to mature firms and growth firms, growth firms are hold relatively higher levels of cash than mature firms, but the findings varied with the choice of growth measure. In general, all selected determinants are significant for cash holdings except for capital expenditures. Further, the results show that large firms with good growth opportunities, but pay less dividend are tend to hold more cash, which is basically in line with previous studies. In the further study, this paper has come to a conclusion that both pecking order and trade-off theories play important role in explaining UK firms’ cash holdings.